Arginase Inhibitors: A Rational Approach Over One Century. Issue 3 (15th November 2016) - Pudlo, Marc; Demougeot, Céline; Girard‐Thernier, Corine
Abstract: Arginase (EC 3.5.3.1) is the bimanganese enzyme that converts L‐arginine into ornithine and urea. This enzyme was discovered more than a century ago and early α‐amino acids were identified as weak inhibitors. It was only during the 90s, after nitric oxide (NO) was reported as one of the most important biological mediators and when tight interrelation of arginase and NO synthase was found, that the development of arginase inhibitors was accelerated. The regulation of arginase activity by the N ‐hydroxy‐L‐arginine (3, NOHA) intermediate of the NO synthesis was the starting point of the N ‐hydroxy‐nor‐arginine (21, nor‐NOHA) that proved to be the first micromolar inhibitor. The previously known manganese and arginase binding by borate inspired the 2( S )‐amino‐6‐boronohexanoic acid (39, ABH) and S ‐(2‐boronoethyl)‐L‐cysteine (40, BEC) now both considered as reference compounds in arginase inhibition. The high‐resolution crystal structure of arginase and molecular modeling has rendered possible the recent design of (53) the strongest α, α‐disubstituted derivatives of ABH. Simultaneously, traditional medicinal plants have contributed as a source of molecular diversity to the discovery of arginase inhibitors. This rational, step‐by‐step approach serves as guide in the present review where emphasis is placed on structure activity relationships. Highlights exhaustive review on arginase inhibitors highlight is made on rational approach to conception and structure activity relationships evaluation model is systematically mentioned with results.